2020
DOI: 10.1111/jce.14802
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial versus epicardial left atrial appendage exclusion for stroke prevention in patients with atrial fibrillation: Midterm follow‐up

Abstract: Background: Left atrial appendage closure (LAAC) became an alternative method for stroke prevention in patients with non-valvular atrial fibrillation (AF) intolerant to long term oral anticoagulation therapy. This study aimed to compare endocardial (Amulet and LAmbere occluders) and epicardial (Lariat) LAAC techniques.Methods: A retrospective, observational case-control study included 223 consecutive CHA 2 DS 2 -VAS score-matched patients with AF who underwent LAAC in two centers.Results: There were 55 matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
(123 reference statements)
0
14
0
Order By: Relevance
“…Endocardial LAAC also demonstrated different concentrations of natriuretic peptides during the follow-up period [ 5 , 9 , 10 ], possibly due to a different extent of leakage around the device and the absence of acute and chronic LAA necrosis. Mechanistically, epicardial LAAC is different from endocardial LAAC [ 11 ]. Epicardial LAAC leads to inflammation of the LAA, which is later followed by fibrosis, scarring, closure, and permanent resorption of the LAA over a prolonged period [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endocardial LAAC also demonstrated different concentrations of natriuretic peptides during the follow-up period [ 5 , 9 , 10 ], possibly due to a different extent of leakage around the device and the absence of acute and chronic LAA necrosis. Mechanistically, epicardial LAAC is different from endocardial LAAC [ 11 ]. Epicardial LAAC leads to inflammation of the LAA, which is later followed by fibrosis, scarring, closure, and permanent resorption of the LAA over a prolonged period [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data has shown good long-term results with acceptable complication rates, even in elderly populations [ 27 ]. The procedure can be performed by endocardial or epicardial approaches with a similar mid-term follow-up [ 28 ]. Results from a nationwide study in the United States indicated that endocardial approach seemed to have a lower complication rate than the epicardial approach [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sealing leaks with occluders may be a reasonable option in this scenario [ 202 ]. Compared to endocardial LAAC devices, the LARIAT system is associated with a higher short-term complication rate [ 203 ], but similar mid-term efficacy [ 204 ]. The second-generation LARIAT + has improved features, such as snare expansion from 40 mm to 45 mm, the addition of a platinum–iridium ‘L’ Marker that allows identification of the device orientation under fluoroscopy, and a stainless steel wire braid on catheter shaft that provides improved ‘torque-ability’ of the catheter.…”
Section: Left Atrial Appendage Closurementioning
confidence: 99%